2023
DOI: 10.1186/s13014-023-02259-8
|View full text |Cite|
|
Sign up to set email alerts
|

Application of four-dimensional cone beam computed tomography in lung cancer radiotherapy

Abstract: Objective This study explored the application of four-dimensional cone beam computed tomography (4D CBCT) in lung cancer patients, seeking to improve the accuracy of radiotherapy and to establish a uniform protocol for the application of 4D CBCT in radiotherapy for lung cancer. Methods 4D CBCT was applied to evaluate tumor volume response (TVR), motion, and center coordinates during radiotherapy in 67 eligible individuals with lung cancer diagnoses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Due to the long acquisition time, patient anatomical motion, mostly respiration (3–5 s per breathing cycle), results in artifacts and blurriness in the reconstructed CBCTs (Rit et al 2011 ). To address the artifacts and resolve the underlying motion, four-dimensional (4D)-CBCT was developed as the current clinical state-of-the-art (Sonke et al 2005 , Zhang et al 2013 , Abulimiti et al 2023 ). 4D-CBCT sorts the projections into a pre-defined set of motion bins and stacks semi-static CBCTs reconstructed from each bin to represent an averaged motion pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the long acquisition time, patient anatomical motion, mostly respiration (3–5 s per breathing cycle), results in artifacts and blurriness in the reconstructed CBCTs (Rit et al 2011 ). To address the artifacts and resolve the underlying motion, four-dimensional (4D)-CBCT was developed as the current clinical state-of-the-art (Sonke et al 2005 , Zhang et al 2013 , Abulimiti et al 2023 ). 4D-CBCT sorts the projections into a pre-defined set of motion bins and stacks semi-static CBCTs reconstructed from each bin to represent an averaged motion pattern.…”
Section: Introductionmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that the second author ‘Xu Yang’ should be co-first author with ‘Muyasha Abulimiti’.…”
mentioning
confidence: 99%